Cost benefit analysis of heroin maintenance treatment - Gutzwiller, Felix 1948-; Steffen, Thomas 1961- (Medical prescription of narcotics, 2000)
The book series "Medical Prescription of Narcotics" gives an account of the research reports of a Swiss study on prescription of narcotics to chronic heroin addicts. In this second volume the results are examined from an economical standpoint.The four main aspects analyzed are housing, work, legal behavior and health. The benefits are rated according to the changes in the quantified effects for the participants followed for one year after entry to the trial. The assessment of the partial benefits is expressed per participant and per day and subsequently added to find the overall benefit. These results are compared with the costs of labor, narcotics, medical needs, and further operating costs of the project.The book is a stimulating contribution to the discussion on heroin maintenance, and provides essential arguments for decision makers in public health, politicians, administrators, physicians, therapists and social workers dealing with drug addicts